2013
DOI: 10.1186/2047-2382-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain management in temperate regions: is multifunctionality enhancing biodiversity?

Abstract: Background: Floodplains are among the most diverse, dynamic, productive and populated but also the most threatened ecosystems on Earth. Threats are mainly related to human activities that alter the landscape and disrupt fluvial processes to obtain benefits related to multiple ecosystem services (ESS). Floodplain management therefore requires close coordination among interest groups with competing claims and poses multi-dimensional challenges to policy-makers and project managers. The European Commission propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…The research question 'Impact of multifunctional floodplain management on biodiversity and ecosystem services' was tackled by several methodological approaches in the frame of the trial assessment 'conservation case' for testing functionality and performance of the science-policy interface BiodiversityKnowledge, (Schindler et al 2013a(Schindler et al , b, 2014. The focus of the trial assessment was on temperate Europe, because floodplains under other climatic regimes, such as boreal or Mediterranean, have basic differences in their floodplain ecology and dynamics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research question 'Impact of multifunctional floodplain management on biodiversity and ecosystem services' was tackled by several methodological approaches in the frame of the trial assessment 'conservation case' for testing functionality and performance of the science-policy interface BiodiversityKnowledge, (Schindler et al 2013a(Schindler et al , b, 2014. The focus of the trial assessment was on temperate Europe, because floodplains under other climatic regimes, such as boreal or Mediterranean, have basic differences in their floodplain ecology and dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…However, European-wide systematic reviews could only be framed and initiated in the frame of the 'BiodiversityKnowledge'-trial assessments (Araújo et al 2013;Schindler et al 2013a, b), but had to be finalized with additional resources afterwards (Bertocci et al 2015). Despite significant interest at the beginning, efficient implementation of the systematic review on biodiversity impacts of floodplain management was hindered by the experts' lack of familiarity with the approach and the need for an intensive and time consuming examination of the methodological demands (CEE 2013) and the specific settings developed for the particular systematic review on effects of floodplain management (Schindler et al 2013a). …”
Section: Insights For 'Biodiversityknowledge'mentioning
confidence: 99%
“…(Schindler et al 2013a) and a systematic map including 70 articles addressing this topic ( Fig. 3a; Schindler et al 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the knowledge synthesis process works in general for the implementation of assessments. In collaboration with requesters and knowledge holders, a number of relevant assessments were produced (Araújo et al 2013Schindler et al 2013aSchindler et al , b, 2014Bertocci et al 2015;Dicks et al 2016). The process is user friendly and flexible, though the methods to be applied are subjected to the constraints of financial resources and time frame .…”
Section: Discussionmentioning
confidence: 99%
“…For studies assessing the management efficiency of several management options, the scoring might be different for each conducted analysis, because sampling effort might vary across considered taxa or some of the primary analyses and results may be presented incompletely. The particular system developed for the purpose of this review considers the features recommended by Bilotta et al [61] and was adapted from the quality assessment system developed by Schindler et al [62]; it will be based on an evaluation of the following criteria (cf. i.…”
Section: Study Quality Assessmentmentioning
confidence: 99%